2016
DOI: 10.3389/fendo.2016.00030
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Remodeling: Its Role in Energy Metabolism and Metabolic Disorders

Abstract: The adipose tissue is a central metabolic organ in the regulation of whole-body energy homeostasis. The white adipose tissue functions as a key energy reservoir for other organs, whereas the brown adipose tissue accumulates lipids for cold-induced adaptive thermogenesis. Adipose tissues secrete various hormones, cytokines, and metabolites (termed as adipokines) that control systemic energy balance by regulating appetitive signals from the central nerve system as well as metabolic activity in peripheral tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
804
1
36

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 946 publications
(905 citation statements)
references
References 205 publications
(274 reference statements)
9
804
1
36
Order By: Relevance
“…The hypertrophy of adipocytes in the visceral WAT is correlated with a high incidence of metabolic disorders. The hypertrophy of adipocytes in the visceral WAT increased basal fatty acid release, pro-inflammatory cytokine release, immune cell recruitment, hypoxia, fibrosis, decreased adiponectin, and impaired insulin sensitivity [1]. ELE and ASP could be beneficial for curbing metabolic disorders, as they prevent these harmful effects, which are caused by the hypertrophy of adipocytes in the visceral WAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypertrophy of adipocytes in the visceral WAT is correlated with a high incidence of metabolic disorders. The hypertrophy of adipocytes in the visceral WAT increased basal fatty acid release, pro-inflammatory cytokine release, immune cell recruitment, hypoxia, fibrosis, decreased adiponectin, and impaired insulin sensitivity [1]. ELE and ASP could be beneficial for curbing metabolic disorders, as they prevent these harmful effects, which are caused by the hypertrophy of adipocytes in the visceral WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing obesity has a beneficial influence on not only health problems, but also economic problems. Obesity is characterized as hypertrophy and proliferation of adipocytes in white adipose tissue (WAT) [1,2]. Eucommia leaf extract (ELE) has been reported to have various bioactive properties [3][4][5][6][7][8][9][10][11], such as anti-obesity effects [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Large adipocytes are dysfunctional due to the in-creased secretion of pro-inflammatory factors, reduced secretion of the protective hormones (insulin, estrogen and adiponectin), which increases the presence of chronic subclinical inflammation, and dysregulation of metabolic homeostasis. On the other hand, in hypertensive state, the formed "circulus vitiosus" is easily maintained by the upregulated levels of proinflammatory cytokines and adipokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical site where the excess calories are preferentially stored as triglycerides plays a pivotal role in the occurrence of metabolic abnormalities [33]. The adipose tissue has been recognized as the main site for lipid accumulation when excess calories are ingested [34]. However, studies have also shown that a positive energy balance over time leads to an increased accumulation of lipids (in the form of triglycerides) in various organs, including the liver, skeletal muscle and pancreas [35].…”
Section: Cytokines and Adipokines In Obesity And Type 2 Dmmentioning
confidence: 99%